P0456LONG TERM PATIENT SURVIVAL AND RELAPSE RATE IN ANCA ASSOCIATED PATIENTS WITH RENAL INVOLVMENET - DATA FROM CROATIAN REFERRAL CENTER. (6th June 2020) - Crnogorac, Matija; Brechelmacher, Ana; Horvatić, Ivica; Kacinari, Patricia; Tišljar, Miroslav; Toric, Luka; Senjug, Petar; Zagorec, Nikola; Galešić Ljubanović, Danica; Galesic, Kresimir
Abstract: Background and Aims: The aim of the research was to evaluate patient and renal as well as relapse free survival in ANCA associated vasculitis (AAV) patients in our center. Despite the advances in understanding pathogenesis of AAVs and advances in treatment, the outcomes of AAV patient differ in various centers. Method: This study included 106 consecutive AAV patients with renal involvement in the period from 2007-2017. We performed renal biopsy on patients using automatic 16 Gauge needle. Light, immunofluorescent and electronic microscopy were performed. All the patients were treated with cyclophosphamide and steroids in induction treatment with adjuvant PLEX and dialysis depending on renal function and lung manifestations. Primary outcomes were combined outcome progression to end-stage renal disease, defined as persistent (more than three months) need for renal replacement therapy or permanent reduction of EGFR to <15ml/minute (according to CKD EPI formula) and/or death (ESRDD), death (D) and ESRD alone, and disease relapse. Kaplan Meyer survival analysis and multivariate Cox proportional hazard regression analysis were used to explore difference between phenotypes and finding significant predictors regarding outcomes. Out of 106 patients (55, 6% female, median age 61; IQR 51-70) there were 66 (61, 1%) microscopic poliangitiis (MPA), 20 (18, 5%) granulomatosis with angitiis and 20 (18, 5%) with renal limited vasculitis (RLV), There were 14 (13%) PR3-ANCA positive patients, 57 (52, 8%) MPO ANCA positive, 5 (4, 6%) PR3-ANCA+MPO-ANCA positive and 32 (29, 6%) ANCA negative patients. Histologically (Berden classification) 43 (39, 8%) patients had crescentic, 19 (17, 6%) focal, 34 (31, 5%) mixed and 12 (11, 1%) sclerotic class. Follow up time ranged from 1 to 127 months. Median follow up time was 21 months (IQR = 7-44). Median time to diagnosis was 3 months (IQR 2, 0-6, 0). Results: During follow up 21 (19, 8%) patients died, 26 (24, 5%) patients reached ESRD and 10 (9, 4%) patients relapsed. There was no significant difference in outcomes between clinical, serological or histological phenotypes. In multivariant analysis independent predictors for death were age (HR = 1, 059, 95% CI =1, 001-1, 120; p = 0, 046), anemia (HR = 0, 952, 95% CI =0, 908-0, 998; p = 0, 040) and BVAS (HR = 1, 093, 95% CI =1, 030-1, 159; p = 0, 003), for ESRD. the need for acute dialysis (HR = 4, 674, 95% CI =1, 996-10, 946; p = < 0, 001), and interstitial fibrosis and tubular atrophy (IFTA) percentage over 50% (HR = 2, 652, 95% CI =1, 157-6, 081; p = 0, 021). and for relapse rate younger age (HR = 0, 924, 95% CI = 0, 870-0, 981; p =0, 010), lower serum creatinine levels (HR = 0, 996, 95% CI = 0, 992-1, 000; p = 0, 033), and the need for acute dialysis (HR = 59, 545, 95% CI =3, 467-1022, 665; p = 0, 005). Event free survival after 12, 24, 36 and 60 months was for death 83, 9, 81, 2, 79 and 74, 7%, for ESRD 80, 6, 77, 9, 76, 1 and 71% and for relapse 95, 3, 88, 4, 88, 4 and 85%. Conclusion: Timely diagnosis and treatment can ensure better outcomes in AAV patients. Though there is an overlap in predictive factors between different cohorts, there are still distinctive differences especially between cohorts from clinical trials and those from observational studies. Our study is among few to show significance of anemia as clinical predictor and IFTA percentage as pathohistological predictor.